European Survey on Adverse Systemic Reactions in Allergen Immunotherapy (EASSI): a real‐life clinical assessment. Issue 3 (10th November 2016) - Calderón, M. A.; Vidal, C.; Rodríguez del Río, P.; Just, J.; Pfaar, O.; Tabar, A. I.; Sánchez‐Machín, I.; Bubel, P.; Borja, J.; Eberle, P.; Reiber, R.; Bouvier, M.; et al.
Abstract: Background: Outside clinical trials, data on systemic reactions (SRs) due to allergen immunotherapy (AIT) are scarce. Methods: A prospective, longitudinal, web‐based survey of 'real‐life' respiratory allergen immunotherapy (AIT) clinical practice was conducted in France, Germany and Spain. SRs were recorded and coded according to the Medical Dictionary for Regulatory Activities (MedDRA) and risk factors associated with SRs were identified. Results: A total of 4316 patients (corresponding to 4363 ongoing courses of AIT) were included. A total of 109 SRs were recorded, and 90 patients (2.1%) presented at least one SR. Most of the SRs occurred in subcutaneous allergen immunotherapy (SCIT) (89%, n = 97). The most frequently reported symptoms were urticaria, rhinitis, dyspnoea and cough. Respiratory symptoms appeared before skin symptoms. Most SRs occurred during the up‐dosing phase (75.8%) and were mild in severity (71.6%). Intramuscular adrenaline was administered in 17 SRs, but only 65% of these were subsequently classified as anaphylaxis. Independent risk factors for SRs during SCIT were as follows: the use of natural extracts (odds ratio, OR) [95% confidence interval (CI)] = 2.74 [1.61–4.87], P = 0.001), the absence of symptomatic allergy medications (1.707 [1.008–2.892], P = 0.047), asthma diagnosis (1.74 [1.05–2.88], P = 0.03), sensitization to animal dander (1.93 [1.21–3.09], P = 0.006) or pollen (1.16 [1.03–1.30], P = 0.012) and cluster regimens ( vs rush) (4.18 [1.21–14.37], P = 0.023). A previous episode of anaphylaxis increased the risk for anaphylaxis in SCIT (OR [95% CI] = 17.35 [1.91–157.28], P = 0.01). Conclusion: AIT for respiratory allergy is safe, with a low number of SRs observed in real‐life clinical practice. A personalized analysis of risk factors could be used to minimize SRs. Abstract :